Classification of Data From Icelandic Financial Statements - Carsten Petersen 1975-; Róbert Gunnarsson 1963-; Sigurrós Soffía Kristinsdóttir 1979- (2014)
Heildartexti lokaskýrslu. Prentuð útgafa og öll fylgiskjöl á CD eru varðveitt í bókasafni HR Financial reports tell the financial story of a company, it is valuable information for anyone who might be interested in investing in these companies. In Iceland these reports are only available in PDF format and they only follow a loosely defined structure. Kóði is a company that would like to be able to extract and work with the data contained in these reports. In this report we look at the feasibility of using machine learning techniques to extract and classify data from Icelandic financial reports. Kóði ehf